2023
DOI: 10.1111/jvh.13809
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐155 regulates M2 polarization of hepatitis B virus‐infected tumour‐associated macrophages which in turn regulates the malignant progression of hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) initiated by hepatitis B virus (HBV) infection is a complicated process. MiR‐155 can alter the immune microenvironment to affect the host's anti‐infective ability. This study investigated the mechanism by which miR‐155 affects tumour‐associated macrophage (TAM) polarization at a molecular level, thus affecting the malignant progression of HBV+HCC. MiR‐155 and TAM‐related cytokine expression were analysed by qRT‐PCR. The distribution of TAMs was detected by immunohistochemistry. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In addition, TAMs are involved in crosstalk with CSCs in various types of tumors 61 . M2-type TAMs promote cancer stem-like properties in tumors, including hepatocellular carcinoma 62 , breast cancer 63 , non-small cell lung cancer 64 , pancreatic ductal adenocarcinoma 65 , and glioblastoma multiforme 66 . Mitchum et al showed that ablation of CCR2 or CSF-1R signaling significantly blocked TAM infiltration in pancreatic ductal adenocarcinoma (PDAC), reduced the number of CD44 + ALDH1 + CSCs, and improved the response to chemotherapy 67 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TAMs are involved in crosstalk with CSCs in various types of tumors 61 . M2-type TAMs promote cancer stem-like properties in tumors, including hepatocellular carcinoma 62 , breast cancer 63 , non-small cell lung cancer 64 , pancreatic ductal adenocarcinoma 65 , and glioblastoma multiforme 66 . Mitchum et al showed that ablation of CCR2 or CSF-1R signaling significantly blocked TAM infiltration in pancreatic ductal adenocarcinoma (PDAC), reduced the number of CD44 + ALDH1 + CSCs, and improved the response to chemotherapy 67 .…”
Section: Discussionmentioning
confidence: 99%
“…The use of bioinformatics to search for potential therapeutic targets that can be used in the treatment of liver cancer is of great significance. Liver cancer is one of the most common malignancies in China, ranking 4th among new cancer cases and second among cancer deaths according to data on malignancies released by the National Cancer Center [22][23][24]. Cancer has become a serious threat to human health, and there are varying degrees of morbidity due to cancer around the world [25].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, PLAU also had certain positive correlations with the immune checkpoint-associated molecules CTLA4, PDCD1, and CD274. Previous studies have also shown that immune cells play an important role in the biological events of LIHC, such as miR-155 regulating M2 polarization of tumor associated macrophages infected with hepatitis B virus, thereby regulating the malignant progression of hepatocellular carcinoma ( 20 ). CD8 + CD226 high T cells in liver metastasis determine the prognosis of colorectal cancer patients receiving chemotherapy and radical surgery treatment ( 21 ).…”
Section: Discussionmentioning
confidence: 99%